Performance Evaluation Of Islamic Mutual Funds In Saudi Arabia: A Case Study - Khelifi, Amina; Barca, Elmehdi; Khelifa, Assia (جامعة الوادي - University of Eloued, 2023)
The purpose of this study is to evaluate the performance of Islamic mutual funds in Saudi Arabia by comparing their risk-return behavior with Tadawul All Share Index during the period from January 2018 to December 2021. we examine their performance by employing several measures such as Sharpe, Treynor, Jensen Alpha and their variants. Our results show that the performance evaluation is sensitive to the benchmark and the performance measures used for comparison. Furthermore, the selection of performance measurement methods depends on the investor's investment objectives, risk tolerance and personal preferences. Moreover, we found that the average returns and volatility of Islamic mutual funds are consistent with the performance of Tadawul All Share Index. This study is important to contribute positively to the development of the Islamic fund management by exploring and employing econometrics modelling to evaluate the investment portfolios
مقال
Keywords: performance evaluation ; Islamic Mutual Funds ; Tadawul All Share Index